Analisis SWOT dan Analisis Stakeholder STEI Hamfara Yogyakarta - Wijiharta Wijiharta (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2018)
Abstract This study aims to determine the position and strategic recommendations of STEI Hamfara. The research method uses a qualitative approach with TOWS analysis and stakeholder analysis. The conclusion of this research is that STEI Hamfara has a unique concept of education and boarding campus which is potential to be developed as a source of excellence and positioning, as well as stakeholder support to take advantage of opportunities and eliminate their weaknesses.